Reversible Photoswitching in Poly(2‐oxazoline) Nanoreactors. Issue 51 (17th August 2020) - Kuepfert, Michael; Qu, Peiyuan; Cohen, Aaron E.; Hoyt, Caroline B.; Jones, Christopher W.; Weck, Marcus
Abstract: This contribution reports light responsive catalytic nanoreactors based on poly(2‐oxazoline) diblock copolymers. The hydrophobic block of the copolymer is a random copolymer consisting of a spiropyran functionalized 2‐oxazoline (SPOx) and 2‐(but‐3‐yn‐1‐yl)‐4, 5‐dihydrooxazole (ButynOx), while the hydrophilic block is based on 2‐methyl‐2‐oxazoline (MeOx). The block copolymer is terminated with tris(2‐aminoethyl) amine (TREN) that serves as catalyst in a Knoevenagel condensation. Four block copolymers with different ButynOx/SPOx and hydrophilic/hydrophobic ratios are synthesized and self‐assembled through solvent exchange. Micelles and vesicles of various sizes are observed by TEM, which undergo morphological and size changes in response to irradiation with UV light. We hypothesize that these transformations in the nanostructures are caused by increases in the hydrophilicity of the hydrophobic block when spiropyran (SP) isomerizes to merocyanine (MC) in the presence of UV light. The reversible transition from micellar to vesicular nanoreactors resulted in increased reaction kinetics through improved substrate accessibility to the catalytic site, or termination of the catalytic reaction due to polymer precipitation. These nanoreactors present a promising platform towards photoregulating reaction outcomes based on changes in nanostructure morphology. Abstract : Here's the change : Photoswitchable amphiphilic poly(2‐oxazoline) nanoreactors incorporating spiropyran and amine catalyst are described. The self‐assembled nanoreactors alter their morphologies in response to UV‐light which in turn manipulates substrate accessibility to the catalytic site.